KUPU-KUPU DALAM KARYA SENI GRAFIS - YUDI EKA PUTRA, Drs. Ismanadi Uska, M.Pd, Dra. Ernis, M.Pd (Serupa The Journal of Art Education, 2015)
Butterflies in the Graphic Work of Art, Fine Art Education, Faculty of Languange and Arts, the State University of Padang. Butterfly is one the organism that created with beautiful color shape. So that it can be an inspiration in the work of art. The purpose of this thesis is (1). To visualize the butterflies in the works of graphic art by showing the beauty of color. (2). To improve the sensitivity and caring of the writer about the neighborhood one of them is butterfly and poured into graphic works. (3). Build a personal extension, by presenting innovative works, creative, have appreciate to the intensity ofgraphic works. (4). Adding references and knowledge of butterflies. There are title of work of butterflies such as friens, night butterflies, leaders, matting, perch, flying, mutual benefit, descent, wings and adventure.Kata kunci: Kupu-kupus, Seni Grafis